Effect of Slaughter Age and Sex on Carcass Characteristics and Composition of Macherla Brown Sheep - Vinaya Babu, P.; Rao, B. Eswara; Rao, T. Srinivasa (Journal of Meat Science, 2014)
Twenty four local Macherla Brown lambs of both sexes in the age group of 9 and 12 months were slaughtered to study the carcass characteristics and composition. Pre-slaughter weight, dressing percent and carcass weight were significantly (P
Keywords: Macherla brown; Carcass characteristics; Sex; Slaughter weight